Improving Dermatology Clinical Efficiency in Academic Medical Centers - Kindley, K. Jade; Jackson, Jeremy D.; Sisson, William Taylor; Brodell, Robert T. (International Journal of Health Sciences, 2015)
Objective: Improve efficiency and profitability in academic medical centers Methods: Academic medical centers across the United States are experiencing lower payments with increasing work hours and patient volumes for many faculty physicians. Department chairpersons find themselves caught in the middle, trying to improve clinical efficiency and profitability while retaining satisfied physicians. During a meeting with the chairperson, one faculty member reported frustration with the inability to meet targets for incentive pay. He agreed to add six slots to his scheduling template each half day if he could have a second LPN/RN for support. The hypothesis: productivity as measured by charges, work relative value units, and collections would increase and be greater than the cost of the additional employee. Data was collected over eight months, with the physician having one assistant during the first half and two assistants during the second half. Results: There was a 30% increase in completed visits, 39% increase in wRVU’s, and 33% increase in gross payments received. Conclusion: This experiment demonstrated that, when allowed to have input regarding structure of their own clinics, physicians are predictably able to see more patients and generate more income.